SPATIO-TEMPORAL ANALYSIS OF NEAR-SURFACE PERMEABILITY ZONE BASED ON RADON GAS CONCENTRATION AND LOCAL LINEAMENT STRUCTURE DENSITY IN WAYANG WINDU GEOTHERMAL FIELD, WEST JAVA - ALI SYAFII (NIM : 22116004), AHMAD
Radon (Rn-222) concentration measurement on the gothermal field is used for trace survey of fluid flow and subsurface structure. Radon concentration has high correlation with local structure. This research was held on the Wayang Windu Geothermal Field using 0.5 m/pixel of high resolution Digital Elevation Model (DEM). Radon concentration relation and lineament structure is necessary for geothermal field exploration, particularly the distribution of permeability zone. Permeability zone determination only uses two data: radon concentration at 17 points shallow drill with 3-5 m of depth measured during 5 periods from 2016 to 2017, and extracted lineament structure density at 20 m/pixel of DEM uses modified Segment Tracing Algorithm (m-STA), consisting of number, length, and intersection of lineament. Lineament density production uses 0.25 ÃƒÂ— 0.25 km2 grid and generates general lineament direction NE-SW and E-W. The geostatistical method: collocated cokriging is used to estimate radon concentration (primary variable) with rare data and lineament (secondary data) with dense distribution data. Radon estimation result has high correlation coefficient with Radon of measurement result. Fuzzy logic approach is held by using 3 criterias of high correlation coefficient value of Radon estimation result with Radon of measurement result, and each lineament density as membership. This method generates 3 permeability zone maps of Wayang Windu Geothermal Field, validated with CoSGSim simulation result, overlayed with geothermal manifestations and regional faults, Radon measurement at NSD points, and also validated by one point near K-13 point. Permeability zone map generates low, moderate, and high permeability zone, and also showed result the of manifestations existence suitability, by affecting structure towards Radon trasportation to surface, mainly at K points.